Entrance skin dose (ESD) and bucky table induced backscattered dose (BTI-BSD) in abdominal radiography with nanoDot optically stimulated luminescence dosimeter (OSLD) - Sayed, Inayatullah Shah; Roslan, Nurul Shuhada; Syed, Waliullah Shah (Cureus, Inc, 2023)
In radiography, inconsistencies in patients' measured entrance skin dose (ESD) exist. There is no published research on the bucky table induced backscattered radiation dose (BTI-BSD). Thus, we aimed to ascertain ESD, calculate the BTI-BSD in abdominal radiography with a nanoDot OSLD, and compare the ESD results with the published data. A Kyoto Kagaku PBU-50 phantom (Kyoto, Japan) in an antero-posterior supine position was exposed, selecting a protocol used for abdominal radiography. The central ray of x-ray beam was pointed at the surface of abdomen at the navel, where a nanoDot dosimeter was placed to measure ESD. For the BTI-BSD, exit dose (ED) was determined by placing a second dosimeter on the exact opposite side (backside) of the phantom from the dosimeter used to determine (ESD) with and without bucky table at identical exposure parameters. The BTI-BSD was calculated as the difference between ED with and without bucky table. The ESD, ED, and BTI-BSD were measured in milligray (mGy). ESD mean values with and without bucky table were 1.97 mGy and 1.84 mGy, whereas ED values were 0.062 mGy and 0.052 mGy, respectively. Results show 2-26% lower ESD values with nanoDot OSLD. The BTI-BSD mean value was found to be approximately 0.01 mGy. A local dose reference level (LDRL) can be established using ESD data to safeguard patients from unnecessary radiation. In addition, to minimize the risk of BTI-BSD in patients in radiography, the search for the use or fabrication of a new, lower atomic number material for the bucky table is suggested.